Geochemical characteristics of hot spring fluids in the Xunwu-Shicheng fault zone of southern Jiangxi - Fuqiang XIAO; Yongjun ZOU; Shuanglong ZHANG; Xing QI; Weidong XIAO (Shuiwen dizhi gongcheng dizhi)
The Xunwu-Shicheng fault zone, located in the eastern part of southern Jiangxi, is a NNE-trending deep fault zone characterized by dense geothermal hot spring activity and frequent seismic events. However, limited research on the characteristics and evolutionary mechanisms of its hot spring fluids has hindered the sustainable development and utilization of geothermal resources. To reveal the geochemical characteristics and origin of hot spring fluids in the fault zone to support the geothermal resource exploration, hot spring water samples and gas samples from nine hot springs were collected. Water chemical composition, gas composition, and isotope analysis of the hot springs were tested by spectrophotometry, chromatography, mass spectrometry, etc. The results show that the hydrochemical types of hot springs in the Xunwu-Shicheng fault zone are mainly HCO3•SO4—Na•Ca and HCO3—Na. The hot springs are formed by the heating of precipitation infiltrating deep thermal storage structures along fault zones. The hot spring water is immature water whose water-rock interaction has not reached equilibrium, and the reservoir temperature is estimated to be 99−143 °C by SiO2 geothermometer. The gas components in hot springs are mainly CO2 and N2, with traces of He. CO2 is mainly derived from inorganic mantle sources, while He originates predominantly from crust, with a secondary contribution mantle. Mantle-derived CO2 and He have significant genetic connections, formed by the upwelling of deep fluids connected by the fault zones. Under the abnormal release of deep mantle fluids in the Xunwu-Shicheng fault zone, the characteristics of hot spring fluids such as thermal storage temperature and mantle gas parameters have a good correspondence between tectonic and seismic activity. The southern section of the fault zone is a favorable area for exploring medium-high temperature geothermal resources. This study provides valuable insights for guiding futher of hot spring resource exploration in the Xunwu-Shicheng fault zone.